Generation of human induced pluripotent stem cell lines HUJIi004 and HUJIi005 from two individuals carrying autosomal-dominant mutations in the CTNBB1 gene resulting in CTNNB1 neurodevelopmental disorder - Daniel J. Steinberg; Kian Maroun; Srinivasarao Repudi; Bruria Ben-Zeev; Rami I. Aqeilan (Stem Cell Research)
Insufficient β-catenin gene activity leads to CTNNB1 neurodevelopmental disorder (CTNNB1-NDD), a prevalent condition causing diverse neurological effects. We derived induced pluripotent stem cell (iPSC) lines from two CTNNB1-NDD individuals. Comprehensive analysis, including karyotyping, sequencing, and functional assays, verified the stem cell properties, genomic stability, identity, and differentiation capabilities. Notably, variable protein expression levels were observed, hinting at potential functional irregularities. in this study we offer valuable groundwork for future research in the field.